Inhibition of TLR4 Signalling-Induced Inflammation Attenuates Secondary Injury after Diffuse Axonal Injury in Rats - Yonglin Zhao; Yahui Zhao; Ming Zhang; Junjie Zhao; Xudong Ma; Tingqin Huang; Honggang Pang; Jiaxi Li; Jinning Song (Mediators of Inflammation)
Increasing evidence suggests that secondary injury after diffuse axonal injury (DAI) damages more axons than the initial insult, but the underlying mechanisms of this phenomenon are not fully understood. Recent studies show that toll-like receptor 4 (TLR4) plays a critical role in promoting adaptive immune responses and have been shown to be associated with brain damage. The purpose of this study was to investigate the role of the TLR4 signalling pathway in secondary axonal injury in the cortices of DAI rats. TLR4 was mainly localized in microglial cells and neurons, and the levels of TLR4 downstream signalling molecules, including TLR4, myeloid differentiation primary response gene 88, toll/IR-1-(TIR-) domain-containing adaptor protein inducing interferon-beta, interferon regulatory factor 3, interferon β, nuclear factor κB (NF-κB) p65, and phospho-NF-κB p65, significantly increased and peaked at 1 d after DAI. Inhibition of TLR4 by TAK-242 attenuated apoptosis, neuronal and axonal injury, and glial responses. The neuroprotective effects of TLR4 inhibition were associated with decreases in the levels of TLR4 downstream signalling molecules and inflammatory factors, including interleukin-1β, interleukin-6, and tumour necrosis factor-α. These results suggest that the TLR4 signalling pathway plays an important role in secondary injury and may be an important therapeutic target following DAI.